Aesthetics of Postmodernism in Clifton Gachagua’s Madman at Kilifi - Adelokun, Adetunji (International Journal of Language and Literary Studies, 2021)
This study is an attempt to analyse the postmodern aesthetics of the poetry collection of Clifton Gachagua. This analysis was informed by the need to critically identify the structure of postmodern writing and the tenets of postmodernism which informs the creative imagination of Clifton Gachagua in Madman at Kilifi. This study critically appraised the manifestation of intertextuality, meaninglessness of meaning (populism), scatological imaging and formlessness in the poetry collection. The study revealed that the poetry collection is a reflection of Clifton Gachagua’s postmodernist inclination and masses oriented ideologies. The poet amplifies the need to advocate the dominance of consumerism and the urgent need to denounce globalization.